Lovell Augustus Reeve (1814–1865): malacological author and publisher - Petit, Richard E. (Zootaxa, 2007)
Lovell Reeve was a major figure in 19 th Century malacology in England. In addition to his monumental Conchologia Iconica, he wrote, among other works, Elements of Conchology, the Conchologia Systematica, and The Land and Freshwater Mollusks Indigenous to, or Naturalized in, the British Isles. He co-authored with Arthur Adams the Mollusca parts of The Zoology of the Voyage of H.M.S. Samarang. Reeve established a printing and publishing firm and produced not only his own works but numerous other natural history books, many finely illustrated. Biographical data are given and his introduction to the study of shells is discussed. That is followed by a short history of his printing and publishing firms which had several name changes over the years. Several contemporaries involved with Reeve in various ways are profiled and his business relationships are briefly treated. Reeve’s early interest in stereographic photography is described. Comments about his descriptions of new species are offered as are the opinions of others on Reeve’s descriptive methods. A few unusual problems involving some of Reeve’s taxa are described as is the manner in which authorship of taxa is treated herein. The major portion of the paper then follows, listing and describing his conchological publications and dating and collating those that were serially published, some never before accurately collated and/or dated. Non-molluscan serial publications that he owned and edited are listed with annotations. A complete bibliography of Lovell Reeve is given for the first time.